2021
DOI: 10.1186/s13256-021-02695-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolamellar hepatocellular carcinoma treated with atezolizumab and bevacizumab: two case reports

Abstract: Background Fibrolamellar hepatocellular carcinoma is a unique tumor of the liver that differs from the classical hepatocellular carcinoma in diagnosis, behavior, and possibly treatment. There is usually absent underlying liver disease, and it usually occurs in young patients. The survival outcomes in localized fibrolamellar hepatocellular carcinoma are perhaps better than in classical hepatocellular carcinoma if treated early and radically. On the other hand, the prognosis remains poor for loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Unfortunately, the treatment did not show any clinical benefits. 56 Several case reports have shown the potential efficacy of immunotherapy in FLC, either with pembrolizumab, 57 nivolumab monotherapy, 58 or combining nivolumab and ipilimumab. 59 There was a retrospective cohort study of patients with FLC identified using the Johns Hopkins Liver Cancer Database, the UT Southwestern 1).…”
Section: Immunotherapymentioning
confidence: 99%
“…Unfortunately, the treatment did not show any clinical benefits. 56 Several case reports have shown the potential efficacy of immunotherapy in FLC, either with pembrolizumab, 57 nivolumab monotherapy, 58 or combining nivolumab and ipilimumab. 59 There was a retrospective cohort study of patients with FLC identified using the Johns Hopkins Liver Cancer Database, the UT Southwestern 1).…”
Section: Immunotherapymentioning
confidence: 99%
“…Current treatments for FL-HCC remain in development. Chemotherapy for unresectable hepatocellular carcinoma (HCC) is a combination of atezolizumab and bevacizumab, but this therapy showed no clinical benefits in case studies in two patients with advanced FL-HCC ( Al Zahrani and Alfakeeh, 2021 ). Sorafenib is another multi-tyrosine kinase inhibitor in use against advanced HCC; however, sorafenib has limited efficacy against FL-HCC, with only delayed progression of disease as the best response ( Ang et al, 2013 ).…”
Section: Ewing Sarcomamentioning
confidence: 99%